INTERNAL CONTROL IN PUBLIC ADMINISTRATION, SOME DETAILS AND REGULATIONS IN PERU - Flores Konja, Julio Vicente (2009)
Common listen to expression into the public management, ours to make «The Office Inner Control», the many it is appreciated to work of applications ours the inner control of the entity. however, to associate well at the office of auditing innery, ours to take called of organ control institution. Then, the regulatory existing, allow also exactly of the inner control, the function of organ control institution and the application of inner control for the better in the public management.